The relative age effect in spanish female soccer players. Influence of the competitive level and a playing position - Sedano, S.; Vaeyens, R.; Redondo, J. C. (Journal of Human Kinetics, 2015)
The purposes of the study were to examine relative age effects (RAEs) in Spanish female soccer and to identify the influence of a playing position. The sample comprised all female players (n=4035) of five different competitive levels in the 2010-2013 seasons: First, Second and Third divisions (n=936, n=1711 and n=870, respectively), and National and Regional (n=232 and n=286, respectively) teams were included. Differences between the observed and expected birth-date distributions were tested based on data from the general Spanish population, using the chi-square statistic followed up by calculating odds ratios and 95% confidence intervals. Results revealed that the birth-date distributions of almost all groups of football players showed an overrepresentation of players born in the first quartile. Only in the lowest level was age distribution not significantly different from that of the general population. Moreover, the RAE risk progressively increased with a higher level of involvement. It was also observed that at some playing positions the birth-date distributions were significantly biased. That was the case for goalkeepers and defenders. It could be concluded that in the current structure of Spanish female soccer there is a relative age effect, probably due to the early processes of talent identification.